2017
DOI: 10.1186/s12974-017-0934-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and immunomodulatory mechanisms of atorvastatin in a murine model of traumatic brain injury

Abstract: Background: Neuroinflammation is an important secondary injury mechanism that has dual beneficial and detrimental roles in the pathophysiology of traumatic brain injury (TBI). Compelling data indicate that statins, a group of lipid-lowering drugs, also have extensive immunomodulatory and anti-inflammatory properties. Among statins, atorvastatin has been demonstrated as a neuroprotective agent in experimental TBI; however, there is a lack of evidence regarding its effects on neuroinflammation during the acute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 59 publications
3
115
0
Order By: Relevance
“…Our method for inducing TBI in mice was described previously [37]. We anesthetized animals with intravenous chloral hydrate (5%, 0.1 ml/10 g) and then fixed them in a stereotactic frame (Kopf Instruments, Tujunga, CA, USA).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method for inducing TBI in mice was described previously [37]. We anesthetized animals with intravenous chloral hydrate (5%, 0.1 ml/10 g) and then fixed them in a stereotactic frame (Kopf Instruments, Tujunga, CA, USA).…”
Section: Modelmentioning
confidence: 99%
“…shown that microglia can be activated after trauma, resulting in increased intracellular caspase-1 and pyroptosis [47], and TBI can also promote microglia polarization [37]. To determine whether VX765 treatment affected microglia polarization and intracellular pyroptosis, changes in relevant markers were detected by immunofluorescence.…”
Section: Microglial Changes After Trauma Previous Studies Havementioning
confidence: 99%
“…In one study delivering recombinant IL-4 after stroke in IL-4 knockout mice, repeated measures were not accounted for and wild-type mice were not tested (52). A variety of other approaches to TBI that promote an M2-like response have also observed improvement in behavioral outcomes (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (31)(32)(33)(34)(35)(36). However, in many of these studies, behavior is not (or could not be) assessed prior to treatment to ensure the absence of accidental bias.…”
Section: Discussionmentioning
confidence: 99%
“…Specific forms of Alzheimer's pathology in which APOE4 is not a risk factor, such as PPA (primary progressive aphasia) with relative sparing of the hippocampal cortex, may be attributable to either localized, repeated trauma (or infection, vascular injury, and so on) to the affected lateral neocortex or to genetic risk factors that are preferentially expressed in affected cells rather than due to effects on amyloid metabolism. Likewise, potential protective factors, such as the use of statins in the context of head trauma, may function by their effects on the microvasculature or glial cells, either of which may operate through mitigation of cell damage, cell division, and cell senescence.…”
Section: Part 3: Addressing Key Questionsmentioning
confidence: 99%